Biotic Index of Dragonflies in The Suranadi Natural Park Area West Lombok - Mohammad Liwa Ilhamdi; Agil Al Idrus; Didik Santoso (Jurnal Pijar Mipa, 2020)
The aims this researc to analyze the biotic index of dragonflies (Odonata) in the Suranadi Nature Park. This research is a descriptive exploratory research. The method used in data collection is the survey method on predetermined transect lines, namely the forest left, right, middle forest and river paths. Data retrieval is done 2 times in 1 month in the morning at 08.00-11.00 WIB and evening at 15.00 - 17.00 WIB. The results showed that the biotic index of dragonflies in Suranadi Nature Park showed that there were 3 species that had the greatest biotic index, namely Gynacantha subinterupta, Zyxomma obtusum and Libelago linearis. There are 13 species that have a biotic index of 0-2. The conclusion is that the dragonfly biotic index in Suranadi Nature Park is more in the 0-2 category, which means that dragonflies still have a wide distribution so they are very commonly found throughout the Suranadi Nature Park.